Time-Resolved Photocurrent Spectroscopy of an LPE-Grown GaAs/AlGaAs Heterojunction Device - Ison, C.; Estacio, E.; Laniog, J.; Salvador, A. (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
GaAs-based devices have recently found widespread use in modern telecommunications. Being a direct band gap semiconductor, GaAs-boasts of better efficiency and faster carrier recombination rates than its more popular indirect-gap silicon counterpart (Sze, 1969). GaAs LED’s, lasers, and photodetectors are the common choice used in fiberoptic communications. Discrete components such as high-electron mobility transistors (HEMT) used in satellite communication are now fabricated using GaAs-based devices (Laniog, 2000). The Condensed Matter Physics Laboratory of the National Institute of Physics, UP Diliman has recently been successful in growing a GaAs/AlGaAs pn heterojunction by Liquid Phase Epitaxy (LPE) (Laniog, 2000). In this paper, the authors present results on the study of the optoelecronic characteristics of this device by photocurrent (PC) spectroscopy. Direct pump-and-probe methods were also employed to measure the transient response of the PC signal of the GaAs/AlGaAs pn junction.